Reindeer control over shrubification in subarctic wetlands: spatial analysis based on unoccupied aerial vehicle imagery - Villoslada, Miguel; Ylänne, Henni; Juutinen, Sari; Kolari, Tiina H. M.; Korpelainen, Pasi; Tahvanainen, Teemu; Wolff, Franziska; Kumpula, Timo (John Wiley & Sons Ltd. on behalf of Zoological Society of London, 2023)
Herbivores can exert a controlling effect on the reproduction and growth of shrubs, thereby counter-acting the climate-driven encroachment of shrubs in the Arctic and the potential consequences. This control is particularly evident in the case of abundant herbivores, such as reindeer (Rangifer tarandus tarandus), whose grazing patterns are affected by management. Here, we tested how different reindeer grazing practices on the border between Finland and Norway impact the occurrence of willow (Salix spp.) dominated patches, their above-ground biomass (AGB) and the ability of willows to form dense thickets. We used a combination of multispectral and RGB imagery obtained from unoccupied aerial vehicles field data and an ensemble of machine-learning models, which allowed us to model the occurrence of plant community types (Overall accuracy = 0.80), AGB fractions (maximum R2 = 0.90) and topsoil moisture (maximum R2 = 0.89). With this combination of approaches, we show that willows are kept in a browsing-trap under spring and early summer grazing by reindeer, growing mostly small and scattered in the landscape. In contrast, willows under the winter grazing regime formed dense stands, particularly within riparian areas. We confirm this pattern using a random forest willow habitat distribution model based on topographical parameters. The model shows that willow biomass correlated with parameters of optimal habitat quality only in the winter grazing regime and did not respond to the same parameters under spring and summer grazing of reindeer.